LAPTM5 potentiates airway remodeling by regulating MAPKs-mediated airway smooth muscle cells’ dysfunction - Lijiao Jiang; Yaping Ying; Haihong Jin; Tingmin Zhou (Mammalian Genome, 2026)

Orbital-hybridized electron bridge enables functional compartmentalization for ultradeep electrosorption - Bijie Bie; Xiaodong Xie; Shuncai Luo; Qingtan Xu; Song Xie; Yaping Miao; Xuming Zhang; Biao Gao; Zhaobo Wang; Buxiao Kuang; Fang Zhou; Liwei Xiong; et al. (Chemical Engineering Journal, 2026)

Integrated prediction of rainfall-induced landslides using zone parameterization and physical-based probabilistic modelling - Renwen Liu; Wei Zhou; Yaping Zhou; Huaqiang Yin; Ming Chen (Geomorphology, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

Pore-scale heat transfer analysis in grain piles via X-ray CT and LBM - Xiaoliang Wang; Ying Zhou; Yaping Shi; Yanbo Hui; Ju Gao; Yihui Wang; Fan Yang (Journal of Food Engineering, 2026)

Rapid particulate microplastics removal from stormwater: Distinct adsorption behavior and data-driven intelligent prediction - Yan Yaping; Song Xichen; Wang Xiaojuan; Liu Xiuyun; Zhou Jianqiang; Wang Gang; Zhang Tingting; Wei Bigui; Zhao Yaqian (Chemical Engineering Journal, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

MnO2/CoFe2O4/PTFE multifunctional catalyst for PM2.5 filtration and visible-light-driven thermocatalytic degradation of toluene - Jupei Zhang; Qiancheng Zhou; Zhuoling Chi; Junying Lü; Yaping Guo (Journal of Environmental Chemical Engineering, 2026)

Optimization of extraction process for active component (dihydromyricetin) from industrial crop vine tea (Ampelopsis grossedentata) and its potential application in functional products for alleviating intestinal inflammation - Zhongxing Chu; Zuomin Hu; Jinping Ding; Yaping Zhou; Feijun Luo; Qinlu Lin (Food Bioscience, 2026)

Enhancing the leaching of copper oxide ores with high contents of calcium-magnesium alkaline bearing gangue by carboxymethyl chitosan - Jinrui Zhou; Wei Guo; Siqi Yang; Xianping Luo; Louyan Shen; Zhiyong Gao; Hongbo Zhao; Yaping Liu (Minerals Engineering, 2026)

Efficient green view index quantification from LiDAR point clouds - Hua Yeyu; Qian Yuguo; Wang Jianhai; Liu Yaping; Zhou Weiqi (Landscape and Urban Planning, 2026)

Controlled Maillard glycation enhances emulsifying performance of plant proteins: Insights from quinoa protein–xylose conjugates - Jinlong Yan; Xiaofang Zhou; Yaping Wang; Benu Adhikari; Wanping Zhang; Zijia Zhang (Innovative Food Science & Emerging Technologies, 2026)

Dynamic changes in rainfall thresholds for post-seismic debris flows using logistic regression and resampling - Renwen Liu; Wei Zhou; Huaqiang Yin; Yaping Zhou; Ming Chen (Bulletin of Engineering Geology and the Environment, 2026)

Deformation and Reconstruction of Coastal Typhoon Wind Fields in Hangzhou Bay - Li Li; Jiayi Guo; Zhiguo He; Tao Feng; Yuezhang Xia; Honghua Zou; Yaping Zha; Rong Zhou; Ye Zhu; Wenjun Zhu (Journal of Marine Science and Engineering, 2026)
Coastal typhoon deformation plays a critical role in determining typhoon tracks, intensity changes, precipitation and related flooding, storm surges, and typhoon waves, and thus is highly associated with coastal disaster patterns. This study proposes a three-level framework for typhoon wind field modeling through the integration of geometric characterization with physical-informed reconstruction. At its core, an elliptical fitting method is developed based on second-order moments to quantify the structural asymmetries. This geometric fitting method is incorporated into the reconstruction method of Holland–Miyazaki, creating a physically consistent model capable of simulating typhoon deformation processes during landfall. Validation through high-resolution Weather Research and Forecasting (WRF) simulations of Typhoon Chan-hom (2015) demonstrates the framework’s effectiveness, capturing elliptical eyewall deformation with aspect ratios exceeding 1.5, primarily driven by coastal topography and surface friction interactions. The method is further validated through Typhoon Mitag (2019), with mean wind component errors below 1 m/s, the average correlation coefficients surpassing 0.9, and wind direction mean absolute errors largely below 10°. This research provides a practical framework for quantifying and characterizing the wind field deformation during typhoon landfall in coastal regions, thereby supporting ther operational forecasting and disaster reduction in vulnerable coastal regions.

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

Transcriptome and eQTL analysis reveal the novel molecular mechanism underlying salt tolerance in the phytochrome B mutant - Conghui Jiang; Yanan He; Lixia Xie; Wen Li; Yaping Li; Yongbin Peng; Jinjun Zhou; Guanhua Zhou; Shasha Wang; Chongke Zheng; Xianzhi Xie (Plant Cell Reports, 2026)

Natural anti-tobacco mosaic virus constituents from plants: A review - Junmei Wang; Juxiang Wang; Shanshan Xiao; Yingshun Miao; Zhengxuan Wang; Jueting Liu; Hongwei Wang; Yaping Liu; Hesham R. El-Seedi; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2026)

Early nut exploitation and its potential for the adaptation of hunter-gatherers to climate change during the LGM in southern China - Qingjiang Yang; Keliang Zhao; Lingxia Zhao; Xinying Zhou; Lili Lu; Yaping Zhang; Lizhao Zhang; Jian Wang; Xinyi Lu; Xiaoqiang Li (Science China Earth Sciences, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

Corrigendum to “Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective” [Toxicol. Lett. 417(2026) 111833] - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Synergistic defense in cotton: Lignin-mediated barriers and JA/ET signaling pathways against Verticillium wilt - Zhixin Liu; Yinpeng Zhang; Yaping Zhou; Baozhen Wang; Jiani Long; Mengyu Liao; Xiaoli Fan; Wenxuan Kang; Beibei Liu; Xuwu Sun (Plant Science, 2026)

Postmarketing adverse events of biologics and Janus kinase inhibitors in patients with atopic dermatitis - Yaping Huang; Qing Zhou; Chengjie Ke; Maohua Chen (Inflammopharmacology, 2026)

Study on the removal and ecological risk of microplastics in road runoff by collapsible loess bioretention facilities - Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; Wei Bigui (Process Safety and Environmental Protection, 2026)

Profiling 32 alkaloid compounds from Macleaya cordata by UPLC-DAD–QTOF-MS/ms - Xinji Zhou; Yuqing Peng; Hao Zhou; Wenyan Wang; Gui Yi; Qi Xia; Yaping Guo; Lianwu Xie (Natural Product Research, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

A novel retrieval of global dust optical depth and effective diameter based on MODIS thermal infrared observations - Jianyu Zheng; Hongbin Yu; Yaping Zhou; Yingxi Shi; Zhibo Zhang; Claudia Di Biagio; Paola Formenti; Alexander Smirnov (Remote Sensing of Environment, 2026)

Construction of platinum/cobalt aluminate heterostructured catalyst via spent catalyst recycling for photo-Fenton-like degradation of malathion - Qiancheng Zhou; Jupei Zhang; Qiuhao Shu; Fengshan Yu; Yaping Guo (Journal of Water Process Engineering, 2026)

High-throughput screening of per- and polyfluoroalkyl substances in human plasma using biocompatible solid-phase microextraction coupled with mass spectrometry via microfluidic open interface - Yaping Li; Emir Nazdrajić; Wei Zhou; Janusz Pawliszyn (Analytica Chimica Acta, 2026)

Interface layer-assisted construction of metal organic framework based porous liquids for high performance CO2 selective separation - Zheng Dong; Yangyang Xin; Bowen Xiang; Ruilu Yang; Menglin Zhu; Baolu Cui; Chenjiao Xie; Shuangshuang Long; Wenwu Zhou; Jianwei Liu; Libing Qian; Hongze Guo; et al. (Journal of Environmental Chemical Engineering, 2025)

FeOOH@HAnB catalyst with exposed (211) facet: High stability and new degradation routes for tetracycline - Yingru Huang; Meiling Zhou; Yaping Zhang; Yufeng He; Yuanyuan Xie; Rongmin Wang (Environmental Research, 2025)

Anti-inflammatory Effects of Membrane Vesicles from Eubacterium rectale via the NLRP3 Signal Pathway - Hongxia Zhang; Yanan Zhao; Dengfu Li; Haixia Li; Zhu Wang; Lu Zhang; Huafeng Niu; Yuchen Huang; Chenchong Zhao; Yaping Jin; Dong Zhou (Probiotics and Antimicrobial Proteins, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

A multi-algorithm fusion approach for identifying post-earthquake rainfall-induced debris flow catchments - Huaqiang Yin; Wei Zhou; Renwen Liu; Yaping Zhou; Ming Chen; Zhangqiang Peng (Bulletin of Engineering Geology and the Environment, 2025)

Transcription factor OxyR regulates peroxidase levels to enhance Brucella's defense against oxidative stress - Yunyi Zhai; Hui Wang; Guangdong Zhang; Bin Li; Ziyang Diao; Lei Chen; Lulu Tian; Feijie Zhi; Junmei Li; Dong Zhou; Wei Liu; Yaping Jin; et al. (Veterinary Microbiology, 2025)

Standardized scale development for fogg behavioral model towards energy-saving behavioral change in buildings - Jiachen Luan; Yaping Zhou; Jun Zhang; Zhun (Jerry) Yu (Energy and Buildings, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Enhanced short-term prediction of urban PM2.5 concentrations by improved hybrid deep learning - Yin Zhou; Yaping Lyu; Xiuli Dang; Roland Bol; Peng Zhang; Na Yu; Yuling Zhang (Journal of Environmental Health Science and Engineering, 2025)

Polysaccharide from discarded tobacco leaves and its anti-TMV activities - Yan Wang; Zhengxuan Wang; Yaping Liu; Charles Brennan; Jueting Liu; Jinhong Zhou; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2025)

K-doped LaAlO3 A-sites: Regulating surface basicity and oxygen species composition for highly efficient organosulfur hydrolysis - Jian Gao; Yu Zhou; Bingran Wang; Wenxuan Luo; Peng Wu; Kai Shen; Yaping Zhang (Journal of Cleaner Production, 2025)

Solid-phase microextraction with recessed matrix compatible coating for in situ sampling of per- and polyfluoroalkyl substances in meat - Yaping Li; Wei Zhou; Runshan Will Jiang; Janusz Pawliszyn (Food Chemistry, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Biochar and PGPR Influence Rhizosphere Bacteria and Synergistically Regulate Tomato Seedling Biomass Under Greenhouse Conditions - Zhenlu Yan; Yuyuan Xing; Changli Ma; Xin Li; Yaping Duan; Xue Wang; Minghao Liu; Muhammad Khashi u Rahman; Xingang Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Permeability prediction of bulk wheat for storage based on micro-computed tomography and lattice Boltzmann method - Xiaoliang Wang; Ying Zhou; Yaping Shi; Qiao Wang; Yanbo Hui; Haiyang Ding (Biosystems Engineering, 2025)

Neonatal Fc receptor participates in endocytosis of Fc fusion protein in vivo and in vitro - Yaping Zhou; Yanfang Wang; Hongmei Zhao; Ting Guo; Yongqing Hao (Veterinary Immunology and Immunopathology, 2025)

The effect of removing bound polyphenols on the physicochemical and functional properties of Rosa roxburghii tratt dietary fiber in vitro - Xiaoli Zhou; Zhicheng Qin; Yan Chen; Yaping Wang; Dong Lin; Lingshuai Meng (Food Bioscience, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

Natural products from Camellia oleifera fruit and its comprehensive utilisation - Yuqing Peng; Hao Zhou; Anlin Zhang; Yaping Guo; Lianwu Xie; Deyi Yuan (Natural Product Research, 2025)

Seismic geomorphology and reservoir conditions of a Middle Miocene submarine channel system in the Taranaki basin, New Zealand - Guangxu Wang; Wei Wu; Quan Li; Weiqing Liu; Yongsheng Zhou; Shiqin Liang; Yaping Sui (Marine and Petroleum Geology, 2025)

Landscape indices explain different responses of runoff and sediment yield to land use/cover change on the Loess Plateau, China - Yanli Qin; Peng Shi; Yuan Hu; Qiang Li; Yaping Wang; Qiaoqiao Wang; Duoduo Zhou (CATENA, 2025)

Targeting gut-liver axis by dietary lignans ameliorate obesity: evidences and mechanisms - Zhongxing Chu; Zuomin Hu; Yi Luo; Yaping Zhou; Feiyan Yang; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Silver nanoparticle-functionalized covalent organic frameworks for the inhibition of foodborne pathogenic bacteria and their application in green grape preservation - Jiayi Zhou; Sai Zhang; Yu Zhang; Tianliang Liu; Shuying Yang; Gaopeng Lv; Yaping Wang; Kewei Feng; Yahong Yuan; Tianli Yue; Qinglin Sheng (Food Chemistry, 2025)

Predictive modeling of river blockage severity from debris flows: Integrating statistical and machine learning approaches with insights from Sichuan Province, China - Wei Zhou; Yaping Zhou; Renwen Liu; Huaqiang Yin; Haowen Nie (CATENA, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Early-onset familial essential tremor is associated with nucleotide expansions of spinocerebellar ataxia in China - Zhilin Zheng; Zeyu Zhu; Jiali Pu; Chen Zhou; Lanxiao Cao; Dayao Lv; Jinyu Lu; Gaohua Zhao; Yanxing Chen; Jun Tian; Xinzhen Yin; Baorong Zhang; et al. (Molecular Biology Reports, 2024)

Targeting gut-brain axis by dietary flavonoids ameliorate aging-related cognition decline: Evidences and mechanisms - Zhongxing Chu; Shuai Han; Yi Luo; Yaping Zhou; Lingfeng Zhu; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

Release of bound phenol from Rosa roxburghii pomace via solid-state fermentation with Trichoderma viride: Mechanisms of change - Yanli Wang; Yaping Wang; Xiaoli Zhou; Bin Du; Yan Chen (Food Bioscience, 2024)

Regulation of nitrogen metabolism by COE2 under low sulfur stress in Arabidopsis - Vincent Ninkuu; Yaping Zhou; Hao Liu; Susu Sun; Zhixin Liu; Yumeng Liu; Jincheng Yang; Mengke Hu; Liping Guan; Xuwu Sun (Plant Science, 2024)

A thermo-hydro-mechanical simulation on the impact of fracture network connectivity on the production performance of a multi-fracture enhanced geothermal system - Zhihong Lei; Yulong Zhang; Xingjie Lin; Yu Shi; Yunhui Zhang; Ling Zhou; Yaping Shen (Geothermics, 2024)

Mid to late Holocene climate changes and grazing activities in northern Loess Plateau, China - Yaping Zhang; Guilin Zhang; Keliang Zhao; Jian Wang; Marika Vicziany; Xinying Zhou; Xiaoqiang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Reduction of heavy metal emissions by adding modified attapulgite to sludge in bubbling fluidized bed incineration process - Zhiyao Li; Junfeng Pang; Yu Zhou; Kai Shen; Yaping Zhang (Fuel, 2024)

Evaluation of the effect of road barriers on wildlife habitats - Yangang Yang; Yun Wang; Hongping Zhou; Xueping Chen; Shuangcheng Tao; Yaping Kong (Transportation Research Part D: Transport and Environment, 2024)

Spartina alterniflora invasion benefits blue carbon sequestration in China - Jingfan Zhang; Dehua Mao; Jihua Liu; Yaping Chen; Matthew Kirwan; Christian Sanders; Jinge Zhou; Zhe Lu; Guoming Qin; Xingyun Huang; Hui Li; Hengqi Yan; et al. (Science Bulletin, 2024)

Biological functions of active ingredients in quinoa bran: Advance and prospective - Feiyan Yang; Tianyi Guo; Yaping Zhou; Shuai Han; Shuguo Sun; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Study on the shale fracture geometry influence on nonlinear gas seepage behavior - Peng Zhou; Haichun Ma; Jiazhong Qian; Xianfa Wei; Yaping Deng (Gas Science and Engineering, 2024)

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

Cracking formation and evolution in surrounding rock of a deep fractured rock mass roadway: A study of the 790-m level segment engineering at the Jinchuan Mine, China - Xiaojun Yu; Yaping Yang; Xifan Li; Huanzhen Luo; Yushan Wang; Xizhi Zhang; Yongyuan Kou; Hongye Li; Yangyi Zhou (Engineering Geology, 2024)

Phytochemical profile and antioxidant characteristics of bound and free phenolics from Rosa roxburghii Tratt - Xiaoli Zhou; Yumeng Qin; Yanli Wang; Yaping Wang; Zhicheng Qin (Food Bioscience, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Synthesis of MnOOH-hydroxyapatite nanowires for degradation of tetracycline - Shenglan Zhao; Meiling Zhou; Jiarui Ren; Yaping Zhang; Yufeng He; Rongmin Wang (Journal of Environmental Chemical Engineering, 2023)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Superior solar water purification achieved by the excellent photothermal conversion and thermal management of porous plasmonic TiN nanoparticles - Yaping Gao; Xiaojie Zhou; Nuo Fu; Sihua Su; Baopeng Ma; Qifeng Ruan; Di Wu; Nan Zhang; Ziwei Deng; Ruibin Jiang (Chemical Engineering Journal, 2023)

Neoproterozoic subduction-related active rifting in the South China Craton: insights from geochemical and zircon Hf isotopic data - Weizhen Tian; Guanghui Wu; Yaping Wang; Yang Shuai; R. Damian Nance; Xiaojun Zhou; Hakro Ahmed Suhail; Chen Zhang; Bo Zheng (International Geology Review, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Facilitating photogenerated carrier transfer and water oxidation kinetics of BiVO4 photoanode via novel Zn@Co3C functional layer - Weibing Li; Liming Wang; Jie Zhou; Ning Wang; Xinyang Fu; Yibo Wang; Yuyu Bu; Yaping Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

AraENCODE: A comprehensive epigenomic database of Arabidopsis thaliana - Zhenji Wang; Minghao Liu; Fuming Lai; Qiangqiang Fu; Liang Xie; Yaping Fang; Qiangwei Zhou; Guoliang Li (Molecular Plant, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Ecological risk assessment of potentially toxic elements in selenium-rich soil with different land-use types - Jinming Zhang; Wen Ge; Chen Xing; Yuan Liu; Xiaofei Shen; Bing Zhao; Xinyu Chen; Yaping Xu; Shoubiao Zhou (Environmental Geochemistry and Health, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Independent and combined effects of exposure to organophosphate esters on thyroid hormones in children and adolescents - Liqin Hu; Bin Zhou; Yaping Li; Lulu Song; Jin Wang; Meng Yu; Xiang Li; Ling Liu; Jing Kou; Youjie Wang; Xijiang Hu; Surong Mei (Environmental Geochemistry and Health, 2023)

The association between organophosphate esters exposure and body mass index in children and adolescents: The mediating effect of sex hormones - Yaping Li; Liqin Hu; Bin Zhou; Zhiyi Zheng; Qitong Xu; Jun Liu; Lulu Song; Youjie Wang; Surong Mei (Chemosphere, 2023)

Improving the uptake of PAHs by the ornamental plant Sedum spectabile using nano-SiO2 and nano-CeO2 - Jianv Liu; Yaping Wang; Mingzhu Wang; Xiaoting Feng; Rongrong Liu; Zijin Xue; Qixing Zhou (Science of The Total Environment, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Unlocking the effects and optimization path of financial support for improvement in environmental quality and rural revitalization development: an empirical analysis based on provincial data of Shaanxi province - Liqian Wei; Yaping Wang; Zizhan Zhou; Jianchao Luo (Environmental Science and Pollution Research, 2023)

Environmental-friendly hydrochar-montmorillonite composite for efficient catalytic degradation of dicamba and alleviating its damage to crops - Chunxia Ding; Guangyong Zeng; Yaping Tao; Xiuyu Long; Daoxin Gong; Nan Zhou; Rongying Zeng; Xiangying Liu; Yaocheng Deng; Mei-E Zhong (Science of The Total Environment, 2023)

Fabrication and characterization of l-ascorbyl palmitate and phospholipid-based hybrid liposomes and their impacts on the stability of loaded hydrophobic polyphenols - Mianhong Chen; Ruyi Li; Xuli Lu; Yaping Dai; Tinghui Chen; Yuhang Xing; Lu Xue; Zhihao Duan; Wei Zhou; Jihua Li (Food Chemistry, 2023)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

PLC1 and H2O2 Mediated the Allelopathic Effect of Oridonin on Root Growth in Arabidopsis thaliana - Yue Zhang; Yanhuang An; Ning Yang; Wei Wang; Ruirui Liu; Run Gao; Yaping Zhou (Journal of Plant Growth Regulation, 2022)

Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Jun Wang; Xuexia Zhu; Yunfei Sun; Lei Gu; Yaping Wu; Yafen Chen; Zhou Yang (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus ( T. obscurus ), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Tracking historical storm records from high-barrier lagoon deposits on the southeastern coast of Hainan Island, China - Liang Zhou; Xiaomei Xu; Yaping Wang; Jianjun Jia; Yang Yang; Gaocong Li; Changliang Tong; Shu Gao (Acta Oceanologica Sinica, 2021)

ADV-Based Investigation on Bed Level Changes Over a Meso-Macro Tidal Beach - Wenhong Pang; Xiaoyan Zhou; Zhijun Dai; Shushi Li; Hu Huang; Yaping Lei (Frontiers in Marine Science, 2021)
Beach intra-tidal bed level changes are of significance to coastal protection amid global climate changes. However, due to the limitation of instruments and the disturbance induced by wave motions superimposed on water levels, it was difficult to detect the high-frequency oscillation of the submerged beach bed level. In this study, an observation, lasting for 12 days and covering the middle tide to the following spring tide, was conducted on a meso-macro tidal beach, Yintan Beach, to simultaneously detect the characteristics and influence mechanism of bed level changes at intra-tidal and tidal cycle scales. The collected data included water depth, suspended sediment concentration (SSC), waves, high-frequency three-dimensional (3-D) velocity, and the distance of the seabed to the acoustic Doppler velocimeter (ADV) probe, which were measured by an optical backscatter sensor, two Tide & Wave Recorder-2050s, and an ADV, respectively. The results showed that the tidal cycle-averaged bed level decreased by 58.8 mm, increased by 12.6 mm, and increased by 28.9 mm during neap, middle, and spring tides in succession, respectively, compared with the preceding tidal regimes. The net erosion mainly resulted from large incident wave heights and the consequent strong offshore-directed sediment transport induced by undertows. Moreover, the variations in the bed level were more prominent during a neap to middle tides than during middle to spring tides, which were jointly caused by the wave-breaking probability regulated by water depth and the relative residence times of shoaling wave, breaker, and surf zones that were determined by relative tidal range. In terms of the intra-tidal bed level, it displayed an intra-tidal tendency of increase during floods and decrease during ebb tides, i.e., the intra-tidal bed level changes were controlled by water depth, which modulated the effects of waves on sediment resuspension and vertical sediment exchange. To be specific, waves and SSC were responsible for the intra-tidal bed level changes under low-energy wave conditions, while mean current and bedform exerted important influences on the variations of the intra-tidal bed level under moderate wave conditions, which broke the foregoing interrelation between bed level, waves, and SSC. This study, therefore, emphasizes the usage of ADV measurement to investigate bed level changes in sandy coasts.

Effects of Exogenous Application of GA4+7 and NAA on Sugar Accumulation and Related Gene Expression in Peach Fruits During Developing and Ripening Stages - Xiongwei Li; Pan Liu; Jingyi Zhou; Mingshen Su; Yaping Ma; Huijuan Jia; Jihong Du; Zhongshan Gao; Zhengwen Ye (Journal of Plant Growth Regulation, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Sodium-induced solid-phase hydrogenation of carbon dioxide to formate by mechanochemistry - Dunfan Zhou; Meng Yu; Yaping Fan; Zhenyu Wang; Guoju Dang; Quansheng Zhang; Jingying Xie (Environmental Chemistry Letters, 2020)

Porphyromonas gingivalis degrades integrin β1 and induces AIF-mediated apoptosis of epithelial cells - Qian Li; Jie Zhou; Li Lin; Haijiao Zhao; Lei Miao; Yaping Pan (Infectious Diseases, 2019)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Myelin Oligodendrocyte Glycoprotein-IgG Contributes to Oligodendrocytopathy in the Presence of Complement, Distinct from Astrocytopathy Induced by AQP4-IgG - Ling Fang; Xinmei Kang; Zhen Wang; Shisi Wang; Jingqi Wang; Yifan Zhou; Chen Chen; Xiaobo Sun; Yaping Yan; Allan G. Kermode; Lisheng Peng; Wei Qiu (Neuroscience Bulletin, 2019)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Purification, characterization, and biocatalytic potential of a novel dextranase from Chaetomium globosum - Liu Yang; Nandi Zhou; Yaping Tian (Biotechnology Letters, 2018)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

The AP2/ERF transcription factor CmERF053 of chrysanthemum positively regulates shoot branching, lateral root, and drought tolerance - Jing Nie; Chao Wen; Lin Xi; Suhui Lv; Qingcui Zhao; Yaping Kou; Nan Ma; Liangjun Zhao; Xiaofeng Zhou (Plant Cell Reports, 2018)

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

Bacterial community temporal dynamics and disease-related variations in the seawater of Pyropia (laver) seedling pools - Xiangyu Guan; Wei Zhou; Chuanming Hu; Miaoxian Zhu; Yaping Ding; Shanshan Gai; Xiaoxuan Zheng; Jianyi Zhu; Qinqin Lu (Journal of Applied Phycology, 2018)

Accumulation and tolerance characteristics of lead in Althaea rosea Cav. and Malva crispa L. - Yaping Huang; Lihong Zu; Meili Zhou; Cong Shi; Guangshuang Shen; Fuchen Shi (Biologia, 2018)

Association of genetic variations in RTN4 3′-UTR with risk for clear cell renal cell carcinoma - Yan Pu; Peng Chen; Bin Zhou; Peng Zhang; Yanyun Wang; Yaping Song; Lin Zhang (Familial Cancer, 2018)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

The relationships between the trends of mean and extreme precipitation - Yaping Zhou; William K.‐M. Lau (International Journal of Climatology, 2017)
This study provides a better understanding of the relationships between the trends of mean and extreme precipitation in two observed precipitation data sets: the Climate Prediction Center Unified daily precipitation data set and the Global Precipitation Climatology Program ( GPCP ) pentad data set. The study employs three kinds of definitions of extreme precipitation: (1) percentile, (2) standard deviation and (3) generalize extreme value ( GEV ) distribution analysis for extreme events based on local statistics. Relationship between trends in the mean and extreme precipitation is identified with a novel metric, i.e. area aggregated matching ratio ( AAMR ) computed on regional and global scales. Generally, more (less) extreme events are likely to occur in regions with a positive (negative) mean trend. The match between the mean and extreme trends deteriorates for increasingly heavy precipitation events. The AAMR is higher in regions with negative mean trends than in regions with positive mean trends, suggesting a higher likelihood of severe dry events, compared with heavy rain events in a warming climate. AAMR is found to be higher in tropics and oceans than in the extratropics and land regions, reflecting a higher degree of randomness and more important dynamical rather than thermodynamical contributions of extreme events in the latter regions.

IL-5 blocks apoptosis and tau hyperphosphorylation induced by Aβ25–35 peptide in PC12 cells - Yuanyuan Zhou; Chaoyan Li; Deheng Li; Yaping Zheng; Jin Wang (Journal of Physiology and Biochemistry, 2017)

Classifying the sedimentary environments of the Xincun Lagoon, Hainan Island, by system cluster and principal component analyses - Yang Yang; Shu Gao; Liang Zhou; Yunwei Wang; Gaocong Li; Yaping Wang; Zhuochen Han; Peihong Jia (Acta Oceanologica Sinica, 2017)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Optimized expression of prolyl aminopeptidase in Pichia pastoris and its characteristics after glycosylation - Hongyu Yang; Qiang Zhu; Nandi Zhou; Yaping Tian (World Journal of Microbiology and Biotechnology, 2016)

NO is involved in spermidine-induced drought tolerance in white clover via activation of antioxidant enzymes and genes - Dandan Peng; Xiaojuan Wang; Zhou Li; Yan Zhang; Yan Peng; Yaping Li; Xiaoshuang He; Xinquan Zhang; Xiao Ma; Linkai Huang; Yanhong Yan (Protoplasma, 2016)

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Single nucleotide polymorphisms in PDCD6 gene are associated with the development of cervical squamous cell carcinoma - Bin Zhou; Peng Bai; Hui Xue; Zhu Zhang; Shaoqing Shi; Kui Zhang; Yanyun Wang; Kana Wang; Yi Quan; Yaping Song; Lin Zhang (Familial Cancer, 2015)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)

Identification and expression profiles of prdm1 in medaka Oryzias latipes - Haobin Zhao; Xiaosha Zhang; Nana Cheng; Jundan Duan; Jialin Wang; Yoshitaka Nagahama; Xueping Zhong; Qingchun Zhou; Yaping Wang (Molecular Biology Reports, 2014)

Prognostic value of IL-27 polymorphisms and the susceptibility to epithelial ovarian cancer in a Chinese population - Zhu Zhang; Bin Zhou; Yuke Wu; Qianqian Gao; Kui Zhang; Yaping Song; Lin Zhang; Mingrong Xi (Immunogenetics, 2014)

Comparative proteomic and physiological analysis of diurnal changes in Nostoc flagelliforme - Wenyu Liang; Lingxia Wang; Yaping Zhang; Xiaoting Lei; Jia Yang; Xiangrong You; Chi-Lien Cheng; Youwen Zhou; Wei Chen (Journal of Applied Phycology, 2013)

Observational climatology and characteristics of wintertime atmospheric blocking over Ural–Siberia - Ho Nam Cheung; Wen Zhou; Yaping Shao; Wen Chen; Hing Yim Mok; Man Chi Wu (Climate Dynamics, 2013)

Revisiting the climatology of atmospheric blocking in the Northern Hemisphere - Ho Nam Cheung; Wen Zhou; Hing Yim Mok; Man Chi Wu; Yaping Shao (Advances in Atmospheric Sciences, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

The Motilin Gene Evolved a New Function in Kangaroo Rats and Kangaroo Mice (Dipodomyinae) - Jing He; Taicheng Zhou; David M. Irwin; Yongyi Shen; Yaping Zhang (Journal of Molecular Evolution, 2012)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Establishment of an aging model of Sca-1+ hematopoietic stem cell and studies on its relative biological mechanisms - Yue Zhou; Bing Yang; Xin Yao; Yaping Wang (In Vitro Cellular & Developmental Biology - Animal, 2011)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)

Atmospheric Corrections Using MODTRAN for TOA and Surface BRDF Characteristics from High Resolution Spectroradiometric/Angular Measurements from a Helicopter Platform - Yaping Zhou; Ken C. Rutledge; Thomas P. Charlock; Norman G. Loeb; Seiji Kato (Advances in Atmospheric Sciences, 2001)

An observational study of the 30–50 day atmospheric oscillations part II: Temporal evolution and hemispheric interaction across the equator - Li Chongyin; Zhou Yaping (Advances in Atmospheric Sciences, 1991)